2006
DOI: 10.1177/0734282905285244
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Theoretical Structure of the Stanford-Binet-Fifth Edition

Abstract: The fifth edition of the Stanford-Binet test went through significant reformulation of its item content, administration format, standardization procedures, and theoretical structure. Additionally, the test was revised to measure five factors important to intelligence across both verbal and nonverbal domains. To better understand these substantial revisions, the underlying factor structure of the instrument was investigated using both exploratory and confirmatory factor analysis procedures across five age group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
61
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 22 publications
20
61
0
Order By: Relevance
“…The g factor accounted for more total and common variance than that accounted for by the four first-order factors combined. These results are also consistent with those obtained from investigations of other intelligence tests, including studies of the Reynolds Intellectual Assessment Scales (Dombrowski, Watkins, & Brogan, 2009;Nelson & Canivez, 2012;Nelson, Canivez, Lindstrom, & Hatt, 2007), Stanford-Binet Intelligence Scales-Fifth Edition (Canivez, 2008;DiStefano & Dombrowski, 2006), Cognitive Assessment System (Canivez, 2011), WlSC-rV (Bodin et al, 2009;M. W. Watkins, 2006M.…”
Section: Discussionsupporting
confidence: 88%
“…The g factor accounted for more total and common variance than that accounted for by the four first-order factors combined. These results are also consistent with those obtained from investigations of other intelligence tests, including studies of the Reynolds Intellectual Assessment Scales (Dombrowski, Watkins, & Brogan, 2009;Nelson & Canivez, 2012;Nelson, Canivez, Lindstrom, & Hatt, 2007), Stanford-Binet Intelligence Scales-Fifth Edition (Canivez, 2008;DiStefano & Dombrowski, 2006), Cognitive Assessment System (Canivez, 2011), WlSC-rV (Bodin et al, 2009;M. W. Watkins, 2006M.…”
Section: Discussionsupporting
confidence: 88%
“…Tbis study's results lends support to tbese criticisms and reaffirms the position against moving much beyond this level of interpretation because of stmctural validity concems (Canivez & Watkins, 2010;DiStefano & Dombrowski, 2006;Dombrowski et al, 2009;Nelson & Canivez, 2012;Watkins, 2010).…”
Section: Conclusion and Implications For Practitionerssupporting
confidence: 76%
“…Correlations among WM tasks (r0.472) are higher than those among STM tasks (r0.392), which suggests that STM reflects more domain-specific characteristics (Kane et al, 2004;Swanson & Howell, 2001 To test Hypotheses 1 and 2, we conducted Model 1 in a two-factor model that distinguishes between STM (Digits, Square Matrix) and WM (Letters and Numbers, and Square Matrix Symmetric) tasks and is based on previous studies (Engle et al, 1999;Kail & Hall, 2001;Kane et al, 2004). We also tested a second model (for Hypothesis 2) with a verbal-numeric (Digits, and Letters and Numbers) and visuospatial (Square Matrix and Square Matrix Symmetric) dual-factor structure covariation (DiStefano & Dombrowski, 2006;Jarvis & Gathercole, 2003;Oberauer et al, 2003;Shah & Miyake, 1996;Vock & Holling, 2008). Our confirmatory factor analysis revealed that Model 2 shows much better fit indices than Model 1, which suggests that verbal-numeric and visuospatial memory span constructs are independent, but share 49% of their common variance.…”
Section: Discussionmentioning
confidence: 98%